The captivating role of calcium in plant-microbe interaction - Bhar, Anirban; Chakraborty, Amrita; Roy, Amit (Frontiers in Plant Science, 2023)
Plant immune response is fascinating due to the complete absence of a humoral system. The adaptive immune response in plants relies on the intracellular orchestration of signalling molecules or intermediates associated with transcriptional reprogramming. Plant disease response phenomena largely depend on pathogen recognition, signal perception, and intracellular signal transduction. The pathogens possess specific pathogen-associated molecular patterns (PAMP) or microbe-associated molecular patterns (MAMP), which are first identified by pattern recognition receptors (PRRs) of host plants for successful infection. After successful pathogen recognition, the defence response is initiated within plants. The first line of non-specific defence response is called PAMP-triggered immunity (PTI), followed by the specific robust signalling is called effector-triggered immunity (ETI). Calcium plays a crucial role in both PTI and ETI. The biphasic induction of reactive oxygen species (ROS) is inevitable in any plant-microbe interaction. Calcium ions play crucial roles in the initial oxidative burst and ROS induction. Different pathogens can induce calcium accumulation in the cytosol ([Ca2+]Cyt), called calcium signatures. These calcium signatures further control the diverse defence-responsive proteins in the intracellular milieu. These calcium signatures then activate calcium-dependent protein kinases (CDPKs), calcium calmodulins (CaMs), calcineurin B-like proteins (CBLs), etc., to impart intricate defence signalling within the cell. Decoding this calcium ionic map is imperative to unveil any plant microbe interplay and modulate defence-responsive pathways. Hence, the present review is unique in developing concepts of calcium signature in plants and their subsequent decoding mechanism. This review also intends to articulate early sensing of calcium oscillation, signalling events, and comprehensive mechanistic roles of calcium within plants during pathogenic ingression. This will accumulate and summarize the exciting roles of calcium ions in plant immunity and provide the foundation for future research.